2021
DOI: 10.1021/acs.jpclett.0c03620
|View full text |Cite
|
Sign up to set email alerts
|

Anion Exchange Doping: Tuning Equilibrium to Increase Doping Efficiency in Semiconducting Polymers

Abstract: High electron affinity (EA) molecules p-type dope low ionization energy (IE) polymers, resulting in an equilibrium doping level based on the energetic driving force (IE-EA), reorganization energy, and dopant concentration. Anion exchange doping (AED) is a process whereby the dopant anion is exchanged with a stable ion from an electrolyte. We show that the AED level can be predicted using an isotherm equilibrium model. The exchange of the dopant anion (FeCl 3 −) for a bis(trifluoromethanesulfonamide) (TFSI −) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 25 publications
0
34
0
Order By: Relevance
“…On the other hand, the fluorine functionalized tetraphenylborate derivatives are more effective in stabilizing the oxidized P3HT owing to the electron withdrawing fluorine atoms. Electrochemical doping of conjugated polymers relies in part on the ability of the electrolyte solution to slightly swell the polymer film, 27,43 which permits counterion penetration to stabilize the electrochemically doped polymer. If the anions in the electrolyte are unable to penetrate into the polymer film, there will be no balance of this positive charge and primarily surface oxidation will occur.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the fluorine functionalized tetraphenylborate derivatives are more effective in stabilizing the oxidized P3HT owing to the electron withdrawing fluorine atoms. Electrochemical doping of conjugated polymers relies in part on the ability of the electrolyte solution to slightly swell the polymer film, 27,43 which permits counterion penetration to stabilize the electrochemically doped polymer. If the anions in the electrolyte are unable to penetrate into the polymer film, there will be no balance of this positive charge and primarily surface oxidation will occur.…”
Section: Resultsmentioning
confidence: 99%
“…and electrochemical doping. 17,26,27 Chemical doping requires matching the energetics of the dopant with the OSC and it is often difficult to control the extent of doping. 28 Alternatively, electrochemical doping works by oxidizing or reducing the OSC through applying a potential to a conductive electrode in an electrochemical cell and balances the charge with the influx of anions (or cations) into the material.…”
Section: Introductionmentioning
confidence: 99%
“…The high carrier density and exchange efficiency achieved here derive primarily from the choice of acetonitrile (AN) as the doping solvent, as opposed to n-butyl acetate used in previous works. [24,39] These improvements stem from AN's high dielectric constant, which increases electrolyte dissociation, and a dramatic increase in the reduction potential of Fe 3+ ions in AN, which enables us to reach high carrier densities.…”
Section: Importance Of Doping Solvent Choicementioning
confidence: 99%
“…Similarly to sequential processing techniques, anion exchange doping utilises molecular dopants in concentrated solutions of electrolytes. (Yamashita et al, 2019;Murrey et al, 2021) Deposition of the anionic exchange solution onto a polymer film allows for the reduced p-type dopant to substitute with the anion from the electrolyte, leading to higher doping levels. Yamashita et al showed that PBTTT doped using anion exchange solutions containing F4TCNQ and LiTFSI as the dopant and electrolyte, respectively, led to conductivities of 620 S cm -1 compared to 260 S cm -1 for just F4TCNQ.…”
Section: P R O V I S I O N a Lmentioning
confidence: 99%